POTENSI PEMANENAN AIR HUJAN DENGAN TEKNIK ROOF TOP RAIN WATER HARVESTING UNTUK KEBUTUHAN DOMESTIK DI KAWASAN RT 12 DESA REJO SARI KOTA PAGAR ALAM - Sela Lusiana; Alharia Dinata; Ali Okta Akbar (P3M Institut Teknologi Pagar Alam, 2023)
Basically, rain water harvesting is defined as a collection of rainwater flows that can be used for domestic household needs, agricultural needs, and environmental management. Rainwater that falls to the earth has two impacts, namely a negative impact and a positive impact. The negative impact of excessive rain can cause disasters such as floods or puddles. The positive impact of rain is that it can be used by humans, be it agriculture, as well as domestic and other needs. Rejo Sari Village Rt 12 is one of the many villages that have difficulty distributing water for domestic needs. This generally occurs in the dry season, while in the rainy season the water is very abundant. then in order to overcome these problems One of them is to analyze the Roof Top Rain Water Harvesting technique or often referred to as rainwater harvesting for domestic needs, the Q obtained at RT 12 Rejosari Village, Pagar Alam City in each house can be seen in table 4.21 above. if the sum of the 62 houses is 542,604 m3/day. with a total catchment area of ​​0.2415 Ha. Based on the results of the calculation and analysis of the potential for rainwater harvesting in the area of ​​Rt 12, Rejo Sari Village, Pagar Alam City, it can be seen in table 5 above that the potential for water that can be harvested from the entire roof of the house is 288,234 liters/day. It can be concluded that this rainwater harvesting technique is not only for the control of runoff but this technique can also be used to harvest rainwater within the scope of domestic needs